The relation between two barriers to self‐compassion and clinical characteristics in individuals with eating disorders. (27th July 2020) - Geller, Josie; Kelly, Allison C.; Samson, Lindsay; Iyar, Megumi M.; Srikameswaran, Suja
Abstract: There is growing support for the role of self‐compassion in recovery from an eating disorder (ED) and two types of barriers have been identified in this population: (a) fears that self‐compassion will result in a failure to meet personal and interpersonal standards (meeting standards); and (b) fears that self‐compassion gives rise to difficult emotions such as grief and unworthiness (emotional vulnerability). Objective: This research examined the relative contribution of meeting standards and emotional vulnerability barriers to the clinical characteristics of individuals with EDs. Method: Participants ( N = 349) completed the fears of compassion for self‐scale, and measures of self‐compassion, ED and psychiatric symptom severity, interpersonal and affective functioning, quality of life and readiness for ED change. Results: Together, the two barrier types accounted for significant variance in all study variables. Meeting standards was associated with lower readiness to change and greater over‐control. In contrast, emotional vulnerability was associated with lower self‐compassion, readiness, and quality of life, poorer interpersonal and affective functioning, and greater ED and psychiatric severity. Conclusion: While both barriers to self‐compassion were related to functioning in individuals with EDs, the emotional vulnerability barrier accounted for more variance in pathology and may be most beneficial to target in treatment.